To Pill or Not to Pill? Access to Emergency Contraception and Contraceptive Behaviour - Ana Nuevo-Chiquero; Francisco J. Pino (Institute of Labor Economics (IZA), 2019)
We examine the effects of free-of-charge availability of emergency contraception on contraceptive behaviour in Chile. Using a survey of individuals 15 to 29, we exploit variation in availability at the municipality level as a consequence of legal and judicial decisions in the late 2000s. We find an increase in the use of emergency contraception in municipalities in which it was available through the public health system, but also an increase in the use of other methods of hormonal, pre-coital contraception, and a decrease of more traditional contraceptive methods. This effect is concentrated among groups with a low starting use of contraceptives, who may benefit from the contact with the health services. Unlike previous results for developed countries, our results indicate that there is scope for an effect of emergency contraception in settings with low starting levels of contraceptive use, and a significant potential for policies to increase adoption of regular contraception.
Keywords: I15; I18; J13; 330; emergency contraception; youth; contraceptive behaviour; risky behaviour